EFFECT OF TAX REVENUE ON ECONOMIC GROWTH IN NIGERIA (Journal of Global Accounting, 2023)
This study assessed the effect of tax revenue on economic growth in Nigeria. Company income tax , petroleum profit tax, personal income tax and value added tax were used to proxy tax revenue, while gross domestic product was used to measure economic growth for a period of twenty eight years spanning from 1994 to 2021.  Based on the objectives of the study, four hypotheses were formulated. Ex-Post facto research design was adopted. The time series data were obtained from Federal Inland Revenue Services, Central Bank of Nigeria, National Bureau of Statistics and the World Bank Publications. As a preliminary step in testing, the study employed the Augmented Dickey Fully Unit root test to confirm the order of integration of the time series variables. The study employed descriptive statistics and inferential statistics using Pearson correlation and Ordinary Least Square (OLS) regression analysis. Specifically, the study found that company income tax has a positive but non-significant effect on Gross Domestic Product (β1=0.000945; p-value = 0.9848>0.05); petroleum profit tax has a positive but non-significant effect on Gross Domestic Product (β2=0.035575; p-value = 0.4857>0.05); personal income tax has a positive but non-significant effect on Gross Domestic Product (β3=0.008635; p-value = 0.9068>0.05); value added tax has a positive but non-significant effect on Gross Domestic Product (β4=0.158820; p-value = 0.2654>0.05) of Nigeria at 5% level of significance. It was recommended that government should diversify the economy for more development in order to increase the overall tax revenue base. The implication of the findings is that an increase in tax revenue will cause economic growth to be improved.
Keywords: Company Income Tax; Petroleum Profit Tax; Personal Income Tax; Value Added Tax; Gross Domestic Product